Basal luteinizing hormone and follicular stimulating hormone: is it sufficient for the diagnosis of precocious puberty in girls? - Dong Seong Lee; Na Yung Ryoo; Sun Hee Lee; Sollip Kim; Jae Hyun Kim (Korean Society of Pediatric Endocrinology, 2013)
PurposeA gonadotropin-releasing hormone stimulation test (GnRHST) is the gold standard in diagnosing central precocious puberty (CPP). The aim of this study was to investigate the diagnostic accuracy of basal gonadotropin levels for girls with suspected precocious puberty and to evaluate the factors affecting positive results of the GnRHST.MethodsKorean girls with early pubertal development who visited the clinic during 2010-2012 were included. Auxological and biochemical tests were evaluated and a standard GnRHST was performed. A peak luteinizing hormone (LH) level of ≥5 IU/L was considered a positive response during the GnRHST.ResultsA total of 336 girls were included. The positive responses were observed in 241 girls (71.7%), and negative responses were found in 95 girls (28.3%). In the logistic regression analysis, the coefficient of the basal LH and basal LH/follicular stimulating hormone (FSH) ratio was 4.23 (P<0.001) and 21.28 (P<0.001), respectively. Receiver operating characteristic analysis showed that the basal LH/FSH ratio is a better predictor of the pubertal result after the GnRHST than the basal LH (area under the curve was 0.745 and 0.740, respectively; P=0.027). Among 189 girls with a basal LH of <0.1 IU/L, 105 (55.6%) had positive responses.ConclusionAn elevated level of the basal LH and basal LH/FSH ratio was a significant predicting factor of positive responses during the GnRHST. However a GnRHST was still necessary for diagnostic confirmation of CPP because more than half of the girls with a basal LH level below the detection limit revealed to have CPP.